Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/scs.0000000000006297
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Different Treatment Modalities of Fracture Zygoma

Abstract: Objectives: This study aimed to determine the pattern of fractured zygoma, different treatment modalities, and complications of the treatment in our center. It also aimed to determine the association between the treatment modalities and complication of treatment, and association between number of fixation and complication. Methodology: A retrospective review was conducted from January 2008 until December 2011. All patients diagnosed with zygomatic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In our study, the fractures were mainly caused by motor vehicle accidents. This correlated with other recent local study that reported road traffic accident as the main etiology (90.8%) of ZMC fractures 7 . In the contrary, others found that the ZMC fracture were most often caused by assaults, 8,9 and falls 10 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the fractures were mainly caused by motor vehicle accidents. This correlated with other recent local study that reported road traffic accident as the main etiology (90.8%) of ZMC fractures 7 . In the contrary, others found that the ZMC fracture were most often caused by assaults, 8,9 and falls 10 .…”
Section: Discussionsupporting
confidence: 90%
“…In another study, there were no significant association between delay of repair and incidence of postoperative facial asymmetry, trismus but statistically significant associations were found between delay and facial scarring and radiographic outcome [33].…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have shown, that under some circumstances, the ORIF of a ZMC fracture can improve the prognosis of a neurosensory deficit. 15,[24][25][26] Other studies have shown that neurosensory function in the ION territory is often improved immediately after reduction, closed or open of a displaced ZMC fracture. 10,23 Furthermore, our results show that surgical treated patients exhibited more neurological symptomatology than observational care.…”
Section: Discussionmentioning
confidence: 99%
“…Our percentages are higher than in this study (48% for CREF, and 100% for ORIF), however, we cannot draw the conclusion in our series about ORIF due to the very limited number of patients. Several studies have shown, that under some circumstances, the ORIF of a ZMC fracture can improve the prognosis of a neurosensory deficit 15,24–26 . Other studies have shown that neurosensory function in the ION territory is often improved immediately after reduction, closed or open of a displaced ZMC fracture 10,23 .…”
Section: Discussionmentioning
confidence: 99%